2012
DOI: 10.1111/dmcn.12020
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive consequences of a paediatric brain tumour and its treatment: a meta‐analysis

Abstract: METHOD Studies were located that reported on performance of PBTS (age range 6-16y).Meta-analytic effect sizes were calculated for Full-scale IQ, Performance IQ, and Verbal IQ as measured by the WISC-III, and mean hit reaction time, errors of omission, and errors of commission as measured by the CPT. Exploratory analyses investigated the possible impacts of treatment mode, tumour location, age at diagnosis, and time since diagnosis on intelligence.RESULTS Twenty-nine studies were included: 22 reported on the WI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
108
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(128 citation statements)
references
References 71 publications
7
108
3
1
Order By: Relevance
“…30 Some photon RT studies have reported declines in Working Memory, 1,4 but such declines were not seen here. Reported impairments in Verbal and Performance IQ 2 cannot be directly compared to the present study because those scores (from the WISC-III) are no longer available in the later edition (the WISC-IV 24 ) used here; however, because the WISC-III Performance IQ includes measures of processing speed, the present results are consistent with reduction in Performance IQ following PRT.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…30 Some photon RT studies have reported declines in Working Memory, 1,4 but such declines were not seen here. Reported impairments in Verbal and Performance IQ 2 cannot be directly compared to the present study because those scores (from the WISC-III) are no longer available in the later edition (the WISC-IV 24 ) used here; however, because the WISC-III Performance IQ includes measures of processing speed, the present results are consistent with reduction in Performance IQ following PRT.…”
Section: Discussionmentioning
confidence: 58%
“…Those reports generally show a progressive cognitive decline that is evident at 1–2 years post-treatment and is more severe for younger age, larger volume of radiation, and higher dose. 1,2 Medulloblastoma studies have estimated annual declines in FSIQ following treatment with photon CSI of between 1.6 and 4.3 points per year, with the better results for older children (age at diagnosis > 7–8 years). 7,8,28,29 One study derived a quadratic model predicting an overall annual decline in FSIQ of about 2 points per year, manifesting in older children after an age-dependent delay (about 2 years for those with mean age 11 years at diagnosis).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreasing sedation use has a long-term effect on the well-being of the child and family by protecting the patient from potential physiological and cognitive deficits [2, 10, 11, 13, 19]. In addition, decreasing sedation use may have financial benefits for the institution.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure precise positioning, sedation may be required. However, daily sedation in children may be associated with risks for respiratory depression, aspiration, central line infections [8, 9], learning disabilities, decreased attentiveness, and decreased cognitive functioning [10, 11]. …”
Section: Introductionmentioning
confidence: 99%